(untitled) (Scientific journal of the Fergana State University, 2023)
Obesity or overweight, which is one of the diseases of the period, is one of the most common conditions today. The presence of this condition affects many physiological functions in the human body. It causes a number of diseases, including cardiovascular, digestive, respiratory and others.